2015
DOI: 10.1007/s00210-015-1110-9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental colitis in mice is attenuated by topical administration of chlorogenic acid

Abstract: Epidemiological data suggest that the consumption of polyphenol-rich foods reduces the incidence of cancer, coronary heart disease, and inflammation. Chlorogenic acid (CGA), an ester of caffeic and quinic acids, is one of the most abundant polyphenol compounds in human diet with proven biological effectiveness both in vitro and in vivo. The aim of the study is to investigate the possible anti-inflammatory effect of CGA in the gastrointestinal (GI) tract and its mechanism of action. We used a well-established m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 42 publications
0
47
0
Order By: Relevance
“…Addition of DSS to drinking water and intracolonic administration of TNBS in mice induce reproducible colitis, and have therefore been used as animal models of IBD to study the efficiency of multiple anti-inflammatory compounds. [10,11,14] In this study, we employed both models to examine the antiinflammatory effects of NanoAg1 and NanoAg2, two aqueous suspensions of nanosilver particles. Our macroscopic and microscopic observations showed that the i.c.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Addition of DSS to drinking water and intracolonic administration of TNBS in mice induce reproducible colitis, and have therefore been used as animal models of IBD to study the efficiency of multiple anti-inflammatory compounds. [10,11,14] In this study, we employed both models to examine the antiinflammatory effects of NanoAg1 and NanoAg2, two aqueous suspensions of nanosilver particles. Our macroscopic and microscopic observations showed that the i.c.…”
Section: Discussionmentioning
confidence: 99%
“…Colon was instantly removed, opened longitudinally, washed with phosphate‐buffered saline (PBS), and immediately examined. Macroscopic colonic damage was assessed using an established semiquantitative scoring system by adding individual scores for ulcers, colonic shortening, and wall thickness, presence of hemorrhage, fecal blood, and diarrhea …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is, however, considered that the effects of coffee are not exclusively due to caffeine but seem to be linked with other specific constituents [77]. Chlorogenic acid displayed a significant anti-inflammatory activity in a well-established mouse model of experimental colitis, as evidenced by a reduction of the macroscopic damage score, myeloperoxidase activity, and inhibition of the NF-κB dependent pathway [78]. Apart from these, the inhibition of cyclooxygenase-2, inducible nitric oxide synthase (iNOS) with the lack of a cytotoxic effect, attenuation of IL-1β and IL-6 along with TNF-α in a dose-dependent manner, and inhibition of NF-κB by chlorogenic acid in a DSS-induced colitis have been reported in a recent study [79].…”
Section: Coffee and Inflammatory Bowel Diseasementioning
confidence: 99%
“…A large group of events are those of a chemical nature, be it in industrial plants or in transport [6][7][8][9][10][11][12]. In chemical events rescuers use protective equipment that protects them from the harmful effects of chemical substances, allowing them to work in a dangerous zone [13][14][15][16][17][18][19]. Wearing a protective suit or respirator, the rescuer must be confident and trustful about the technical condition and reliability of the equipment [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%